2011
DOI: 10.1186/1471-2334-11-234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of praziquantel treatment of Schistosoma mansoni during pregnancy on immune responses to schistosome antigens among the offspring: results of a randomised, placebo-controlled trial

Abstract: BackgroundOffspring of women with schistosomiasis may exhibit immune responsiveness to schistosomes due to in utero sensitisation or trans-placental transfer of antibodies. Praziquantel treatment during pregnancy boosts maternal immune responses to schistosome antigens and reduces worm burden. Effects of praziquantel treatment during pregnancy on responses among offspring are unknown.MethodsIn a trial of anthelminthic treatment during pregnancy in Uganda (ISRCTN32849447; http://www.controlled-trials.com/ISRCTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(52 reference statements)
3
14
0
Order By: Relevance
“…This finding is consistent with our earlier report in which we did not find significant effects of praziquantel treatment during pregnancy on cytokine responses to schistosome antigens among the offspring, in either cord blood or at age one year [3]. Of some interest, however, was the IL-10 response to SWA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is consistent with our earlier report in which we did not find significant effects of praziquantel treatment during pregnancy on cytokine responses to schistosome antigens among the offspring, in either cord blood or at age one year [3]. Of some interest, however, was the IL-10 response to SWA.…”
Section: Discussionsupporting
confidence: 93%
“…For those who are tolerant, this may be due to induction of regulatory mechanisms, or to deletion of schistosome antigen specific cells. When the baby is sensitised in-utero , profiles of infant responses resemble the mothers' responses: mixed type one, type two cytokine responses and a prominent IL-10 response, as shown by our recent study on cord blood responses to schistosome worm (SWA) and egg (SEA) [3] and one earlier study [2]. Our study suggested a direct correlation between maternal S. mansoni infection intensity and cord blood T cell sensitisation of the offspring [3].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Outside of pregnancy, we and others have related these responses to nutritional, hepatic and hematologic morbidities in infected individuals [43][46]. Surprisingly, maternal schistosomiasis during pregnancy elicits a pro-inflammatory response detectable in the neonate [8], and neonates exposed to maternal schistosomiasis during pregnancy display a more robust response to antigenic challenge and have elevated levels of antibodies against schistosome antigens at birth than their unexposed counterparts [13], [47]. Together, these results suggest that maternal schistosomiasis may influence the outcome of initial pediatric schistosome infections acquired during early childhood.…”
Section: Discussionmentioning
confidence: 98%